Analisis Penyeimbangan Beban Transformator Distribusi 400kva 20kv/400v Menggunakan Software ETAP 19.0.1 - Jovan Fathin Fawwas; Syamsir Abduh; Tyas Kartika Sari (Website, 2022)
Research on load imbalance at the distribution transformer substation DK 256 at Perum puri garden aims to reduce the number of load imbalances and the value of electrical power losses. The research method used is the literature method, the observation method, and the interview method. Analysis and calculations to determine the value of losses using ETAP 19.0.1 simulation. From the simulation results of the 19.0.1 ETAP calculation, before the load balancing, the percentage of imbalance at the DK 256 substation was 10.93%. After load balancing, the percentage of unbalance at the DK 256 substation was reduced to 3.64%. For losses that occur in each department at the DK 256 substation after balancing the load it becomes 6.4 kW, reducing the value of losses which is 25.58%. The cost savings from balancing the load at the DK 256 substation against losses flowing to the neutral conductor is Rp. 2,324,172.00/month.Penelitian ketidakseimbangan beban pada gardu transformator distribusi DK 256 di Perum puri garden bertujuan untuk mengurangi angka ketidakseimbangan beban dan nilai losses daya listrik. Metode penelitian yang digunakan adalah metode literatur, metode observasi, dan metode wawancara. Analisis serta perhitungan untuk menentukan nilai rugi-rugi menggunakan simulasi ETAP 19.0.1. Dari hasil simulasi perhitungan ETAP 19.0.1, pada saat sebelum penyeimbangan beban, persentase ketidakseimbangan di gardu DK 256 yaitu sebesar 10,93 %. Setelah penyeimbangan beban, persentase ketidakseimbangan di gardu DK 256 berkurang menjadi 3,64%. Untuk losses yang terjadi pada setiap Jurusan di gardu DK 256 setelah penyeimbangan beban menjadi sebesar 6,4 kW, menghemat energi dari losses sebesar 25,58%. Penghematan energi dari penyeimbangan beban pada Gardu DK 256 terhadap losses yang mengalir pada penghantar netral sebesar Rp 2.324.172,00/bulan.